2017
DOI: 10.1016/j.neuint.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Are nestin-positive mesenchymal stromal cells a better source of cells for CNS repair?

Abstract: In recent years there has been a great deal of research within the stem cell field which has led to the definition and classification of a range of stem cells from a plethora of tissues and organs. Stem cells, by classification, are considered to be pluri- or multipotent and have both self-renewal and multi-differentiation capabilities. Presently there is a great deal of interest in stem cells isolated from both embryonic and adult tissues in the hope they hold the therapeutic key to restoring or treating dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 105 publications
(154 reference statements)
1
27
0
1
Order By: Relevance
“…Such variety in the stem cells and OECs in the OM was also proposed following clinical studies of OM grafts transplanted into regions of SCI (Lima et al, ), and the OM has recently been confirmed as a potential source of adult stem cells (Feron, Perry, Girard, & Mackay‐Sim, 2013; Girard et al, ; Lindsay et al, ; Lindsay, Johnstone, McGrath, Mallinson, & Barnett, ; Lindsay & Barnett, ; Nivet et al, ; Stamegna et al, ; Tome, Lindsay, Riddell, & Barnett, 2009). In addition to OECs, human OM biopsies contain up to 5% mesenchymal‐like stromal cells from the LP.…”
Section: Olfactory Cell Characteristics and Their Origins In The Om Omentioning
confidence: 76%
See 1 more Smart Citation
“…Such variety in the stem cells and OECs in the OM was also proposed following clinical studies of OM grafts transplanted into regions of SCI (Lima et al, ), and the OM has recently been confirmed as a potential source of adult stem cells (Feron, Perry, Girard, & Mackay‐Sim, 2013; Girard et al, ; Lindsay et al, ; Lindsay, Johnstone, McGrath, Mallinson, & Barnett, ; Lindsay & Barnett, ; Nivet et al, ; Stamegna et al, ; Tome, Lindsay, Riddell, & Barnett, 2009). In addition to OECs, human OM biopsies contain up to 5% mesenchymal‐like stromal cells from the LP.…”
Section: Olfactory Cell Characteristics and Their Origins In The Om Omentioning
confidence: 76%
“…In recent years, a stem cell‐like population has been identified in the OE and another one in the LP (Tome et al, 2009). OM‐MSCs have been isolated from the LP and characterized in different laboratories (Delorme et al, ; Feron et al, 2013; Girard et al, ; Lindsay et al, ; Lindsay et al, ; Lindsay & Barnett, ). Transplanted olfactory MSCs differentiated into neurons and stimulated neuroplasticity after lesions in the hippocampus, promoting neurogenesis (Nivet et al, ).…”
Section: Oecs In Spinal Cord Injury (Sci) Repairmentioning
confidence: 99%
“…These stem cells could be differentiated in vitro and be beneficial to perform autologous transplantations or disease modeling [42, 43]. …”
Section: Discussionmentioning
confidence: 99%
“…Dermcidin acts as a neural growth factor [95]; retinoic acid is involved in neurobehavioural disorders and plays a role in normal neural development [96] and Cadherin acts as a regulator of neural cell growth [97]. OM-MSCs were identiied as secreting high levels of the chemokine CXCL12 [98] that is known to be important in the promotion of endogenous myelinations [99]. Evidences that OM-MSCs are capable to alter the biological properties of the precursors of OECs and oligodendrocytes and of increasing the myelination of the oligodendrocytes in the CNS [63], in conjunction with the other indings referred, demonstrate the enormous potential of these cells to be applied in regenerative medicine of the nervous system in general and in the PNS in particular.…”
Section: Secretome and Metabolomementioning
confidence: 99%